Numerical Analysis of the Characteristics of Glass Photonic Crystal Fibers Infiltrated with Alcoholic Liquids - Nguyen, Thuy Thi; Chu, Trang Thi Gia; Le, Minh Van; Tran, Vu Quoc; Nguyen, Manh The; Doan, Khoa Quoc; Dinh, Khoa Xuan; Chu, Lanh Van; Le, Tran Tran Bao (Communications in Physics, 2020)
The characteristics of PCF with various air hole diameters infiltrated with alcoholic liquids such as ethanol, methanol, propanol and butanol are numerically investigated. Based on the numerical results, we have analyzed and compare in detail the characteristics of these fibers including effective refractive index, effective mode area, dispersion and confinement loss for two case: the diameters and lattices constant of air holes are equal 1 µm and 5µm, 1.42µm and 3.26µm, respectively. The PCF infiltrated with ethanol and butanol showed better near zero flattened dispersion property at 1.42µm and 1µm wavelength respectively. With diameters and lattices constant of air holes equal 1.42μm and 3.26μm, the smallest dispersion of PCF filled with ethanol of 5.91075308 (ps.(nm.km)-1) and methanol of 19.3592474 (ps.(nm.km)-1). The highest ZDW of the PCF infiltrated with ethanol and methanol is 1.24604224µm and 1.22405714µm, respectively. Specially, the value of effective refractive index, effective mode area, dispersion and confinement loss decrease in an orderly manner from butanol, propanol, ethanol to methanol and all the alcoholic liquids’s cuvers of dispersion are flat and are very close to each other and near the zero dispersion curve in case the diameters and lattices constant of air holes are equal 1µm and 5µm. The proposed PCF shows a promising prospect in technology applications such as supercontinuum generation